Pemanfaatan Videoscribe Dalam Peningkatan Kompetensi Guru - Tri Astuti Arigiyati; Betty Kusumaningrum; Krida Singgih Kuncoro (Universitas PGRI Adi Buana Surabaya, 2021)
The learning media used by teachers are still relatively simple, such as student worksheets and student books published by the Ministry of Education and Culture and PowerPoint and learning videos that are already on YouTube. Not yet found a teacher who uses VideoScribe and PowerPoint-based multimedia. The majority of PowerPoints are only used as a media presentation with simple features. Learning with the media used by teachers is still not too exciting for students' attention. Students assume that the learning media used by teachers have nothing new that makes students interested in understanding the subject matter. The impact that occurs is the lack of interest, motivation, and enthusiasm of students in participating in learning; consequently, student learning achievement is still below the KKM. The solution to the problem offered is related to the existing problem is the implementation of training activities and mentoring the development of learning media based on Sparkol VideoScribe for Muhammadiyah 4 Yogyakarta Middle School teachers. The effectiveness of this training was measured by the effectiveness questionnaire and the number of teachers who can use VideoScribe.